2013
DOI: 10.3390/ijerph110100390
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Distribution of Four Cacti Species Due to Climate Change in Chihuahua, Mexico

Abstract: Abstract:This study is about four cacti species in the state of Chihuahua, (Coryphantha macromeris, Mammillaria lasiacantha, Echinocereus dasyacanthus and Ferocactus wislizenii). Geographic distribution was inferred with MaxEnt. Projection was estimated under three scenarios simulated from IPCC (A2, B1 and A1B) and four periods (2000, 2020, 2050 and 2080) with 19 climatic variables. MaxEnt projects a species decrease in 2020 under scenario A2, increasing in the following years. In 2080 all species, except E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Although in general cacti should benefit from an increase in CO 2 concentration and temperature rise, extending their poleward and elevation ranges, the impact of climate change should be determined at the specific level (Nobel, 1996). Indeed, niche projections for future climate show that species would respond in specific ways, the predicted distribution areas varying from remaining stable to undergoing a severe contraction (Aragón-Gastélum et al, 2014;Carrillo-Ángeles et al, 2016;Cortés et al, 2014). However, the potential distribution areas may not match potentially colonizable areas, the process being limited by several factors as seed dispersal efficiency, spatial barriers and unconnected distribution areas as observed for Thelocactus hastifer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in general cacti should benefit from an increase in CO 2 concentration and temperature rise, extending their poleward and elevation ranges, the impact of climate change should be determined at the specific level (Nobel, 1996). Indeed, niche projections for future climate show that species would respond in specific ways, the predicted distribution areas varying from remaining stable to undergoing a severe contraction (Aragón-Gastélum et al, 2014;Carrillo-Ángeles et al, 2016;Cortés et al, 2014). However, the potential distribution areas may not match potentially colonizable areas, the process being limited by several factors as seed dispersal efficiency, spatial barriers and unconnected distribution areas as observed for Thelocactus hastifer.…”
Section: Discussionmentioning
confidence: 99%
“…22201/ib.20078706e.2019.90.2246 limiting cactus distribution in the Chihuahuan Desert (Hernández & Bárcenas, 1995). Niche modeling has shown that temperature has the greater influence on the distribution of 4 cactus species in Chihuahua (Cortés et al, 2014), while temperature and precipitation are the main environmental variables constraining distribution of species in the genus Astrophytum Lem. (Carrillo-Ángeles et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that desert succulents have a high tolerance of water and temperature stress (Nobel 2010); however, models of global climate change predict that some cacti species will decrease their distribution range due to increased temperature and diminished rainfall (Butler et al 2012;Cortes et al 2013;Dávila et al 2013;Martorell et al 2015), although these predictions were proposed for adult individuals. Our hypothesis that cacti seedlings located within OTCs will experience a higher mortality rate in field conditions than in control plots was corroborated and supports these predictions for adult plants.…”
Section: Discussionmentioning
confidence: 99%
“…The economic importance and the intense harvest of the wax from candelilla seems to gradually reduce the natural populations of this species [7]. In addition, the species face a possible vulnerability due to climate change, based on the scenarios defined for the near future [9,18,19].…”
Section: Introductionmentioning
confidence: 99%